The philosopher masked as literary theorist: 'cunning intelligence' (metis) instantiated in Bakhtin's rhetorical style - Cook, J (2016)
This dissertation discusses and analyses Mikhail Mikhailovich Bakhtin's conscious strategy of self-fashioning and reinvention, which is realised in his life and supported by the theoretical constructs contained in his Collected Works. It addresses the ambiguities and uncertainties in Bakhtin's life and work and uses two aspects of his philosophical approach and constructs to explicate these inconsistencies: his theory of identity and his theory of language. The analytical tools used to arrive at this conclusion include the notion of reflexivity (using Bakhtin's own theoretical constructs to analyse incidents in his life, and in turn, using those incidents to illustrate the concepts he developed). Theoretical support for Bakhtin's self-fashioning is provided by Fitzpatrick’s theory of reinvention through impersonation and imposture in Revolutionary Russia. Bakhtin's theory of identity (expressed in his Nietzsche-influenced concept of the mask and its associated concept of travesty) supports this reinvention. Bakhtin's notion of double-voicedness, supported by his linguistic theories of interdiscursivity, heteroglossia and the utterance reinforce these two lines of thought. Bakhtin’s two figures of speech: the word with a 'backward glance' «слово с оглядкой» and the word with a 'loophole' «слово с лазейкой» encapsulate this convergence of theory and life. These two constructs are brought into sharp relief when illuminated by Wittgenstein's theory of language-games, Austin's concept of performativity and Benveniste’s formulation of deixis. The overarching metaphor for this dissertation is the Classical Greek concept of metis, or 'cunning intelligence', a concept that is instantiated in the way in which Bakhtin framed the narrative of his life and the manner in which he performed his work. The dissertation concludes that Bakhtin evolved a multi-threaded philosophy which was self-consistent in the way in which it addressed the creation of identity, the expression of language and the performance of life and work through the metaphor of metis.